Education: 2. The Pedagogic Concept Of Creative Imagation Development Of Students-Plastic Artists - Roşca-Ceban Daniela (Sciendo, 2018)
The concept of educational development in the Republic of Moldova reveals the political, social and economic transformations, triggered in the republic, which impose the necessity of drawing new ways of developing the education in a creative perspective. The specific note of the education is the orientation of the activities towards the student, the revealing of the creative potential of development and organization of the instructive educational activity based on strategies of individualization, engaging the divergent thinking.